Responses of defect-rich Zr-based metal–organic frameworks toward NH3 adsorption - Yoskamtorn, T; Zhao, P; Wu, X-P; Purchase, K; Orlandi, F; Manuel, P; Taylor, J; Li, Y; Day, S; Ye, L; Tang, CC; Zhao, Y; et al. (American Chemical Society, 2021)
Understanding structural responses of metal–organic frameworks (MOFs) to external stimuli such as the inclusion of guest molecules and temperature/pressure has gained increasing attention in many applications, for example, manipulation and manifesto smart materials for gas storage, energy storage, controlled drug delivery, tunable mechanical properties, and molecular sensing, to name but a few. Herein, neutron and synchrotron diffractions along with Rietveld refinement and density functional theory calculations have been used to elucidate the responsive adsorption behaviors of defect-rich Zr-based MOFs upon the progressive incorporation of ammonia (NH3) and variable temperature. UiO-67 and UiO-bpydc containing biphenyl dicarboxylate and bipyridine dicarboxylate linkers, respectively, were selected, and the results establish the paramount influence of the functional linkers on their NH3 affinity, which leads to stimulus-tailoring properties such as gate-controlled porosity by dynamic linker flipping, disorder, and structural rigidity. Despite their structural similarities, we show for the first time the dramatic alteration of NH3 adsorption profiles when the phenyl groups are replaced by the bipyridine in the organic linker. These molecular controls stem from controlling the degree of H-bonding networks/distortions between the bipyridine scaffold and the adsorbed NH3 without significant change in pore volume and unit cell parameters. Temperature-dependent neutron diffraction also reveals the NH3-induced rotational motions of the organic linkers. We also demonstrate that the degree of structural flexibility of the functional linkers can critically be affected by the type and quantity of the small guest molecules. This strikes a delicate control in material properties at the molecular level.